Effect of Palm Polysaccharides on Growth Performance, Feed Digestibility and Carcass Percentage of Broilers - Sundu , B.; Bahry, S.; Hatta, U.; Damry, H.B. (International Journal of Poultry Science, 2018)
Objective: A study was conducted to determine the effect of diets supplemented with several palm polysaccharides on chicken performance, fecal moisture, feed digestibility and carcass percentage. Methodology: A total of 168 unsexed broiler chicks were used in this trial. The broiler chicks were kept for 4 weeks. The broilers were then transferred into metabolism cages for 1 week for digestibility and fecal moisture studies. On day 35, the broilers were sacrificed by cervical dislocation for carcass measurements. The broiler chickens were fed with starter (23% protein and 13.39 MJ of metabolizable energy) and grower (21% protein and 13.39 MJ of metabolizable energy) diets. Feed and water were provided ad libitum. Six different types of diets: Control (C), control+2 ppm avilamycin (C+avi), control+0.05% copra polysaccharide (C+cop), control+0.05% salak polysaccharides (C+salak), control+0.05% sugar palm polysaccharides (C+sug palm) and control+0.05% sago polysaccharides (C+sag) were used. A completely randomized design was used with six treatments and four replicates of 7 birds each. Results: The study indicated that diets supplemented with avilamycin, copra polysaccharides and salak polysaccharides increased body weight gain (p